IMPLEMENTASI INTERNET OF THINGS MENGGUNAKAN PLATFORM THINGER UNTUK PEMANTAUAN DAN STERILISASI UDARA PADA RUANGAN - Fariza Haqi (Electro Luceat, 2021)
This research focuses on updating the air monitoring and sterilization system that uses Internet of Things technology like a remote control. This remote control is not limited to smartphones and all devices that can be connected to the internet. This is an advantage of web-based control so that the tools used are much more varied with just one design. This remote control has 2 main functions, namely a monitoring function and a sterilization function. The monitoring function will display the output of sensor reading data from Arduino, namely data on carbon monoxide (CO), carbon dioxide (CO2), and dust intensity. Meanwhile, the sterilization function is in the form of a push button that is used to turn on and off fans and UVC lamps to sterilize the air in the room. Based on the tests and observations carried out, the monitoring and sterilization tools are running well. The output data on the LCD and the Thinger IO platform have the same value. In addition, the connection time needed to be able to connect to WiFi or Thinger is quite good, which is still under 10 seconds. This study has a discussion of remote control with the Thinger IO platform with NodeMCU devices